ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Nurhilal Lapodo; Sulaeman Sulaeman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
This study aimed to determine factors affecting the level of income and the feasibility of wetland rice farming system in Sidera village Sigi Biromaru sub district of Sigi districts. Thirty one respondents determined using a simple random technique was selected from population of 110 farmers.  Income and feasibility analysis were used to analyze data obtained. The results showed that land, seed and fertilizer are highly significant affected the production of the wetland rice farming system. The revenue of the rice farming system in Sidera village Sigi Biromaru sub district of Sigi districts IDR 8,698,064.52/1.29 equal to IDR 6,742,685.67/ha in average with the average total cost of IDR 3,610,086.87/1.29 equal to IDR 2,798,516.95/ha and the average total income of IDR 5,087,979.65/1.29 equal to IDR 3,944,168.72/ha. Keywords: Feasibility, Income, Revenueand  Wetland Rice.